Everyday Theology in Cultural Context: Forgiveness and Grace. Issue 2 (June 2021) - Cook, Kaye V.; LePine, S. Elisha; Chang, Caleb; DeSouza, Adila; Crossett, Carter; Chiou, Grace
Forgiveness is a universal virtue that appears in most cultures and religions but with cultural particularities. The current pilot research uses a mixed-methods approach to describe variations in everyday theologies of forgiveness across culture. Universal understandings of forgiveness were documented among Study 1 participants who represented three American Christian subcultures (Brazilian-Americans, Chinese-Americans, and American students), replicated in Study 2 (with Hong Kong church members and American students). Members of non-American cultures described efforts to reach social harmony by maintaining a culturally appropriate tension between reconciliation and responsibility in relationships, e.g., by demonstrating concerns with saving face, with the impact of violations on the larger community, and for personal responsibility in mitigating interpersonal violations. Differences among participants in these pilot studies were associated with the different cultural histories of the participants' cultures and whether the cultures they represent are broadly categorized as collectivist or individualist.